2013
DOI: 10.5056/jnm.2013.19.2.210
|View full text |Cite
|
Sign up to set email alerts
|

Predictable Marker for Regression of Barrett's Esophagus by Proton Pump Inhibitor Treatment in Korea

Abstract: Background/AimsThere has been no report regarding the regression of Barrett's esophagus (BE) by continuous treatment of proton pump inhibitor (PPI). The aim of this study was to determine the regression rate of BE by PPI and predictable markers related to regression.MethodsThirty-five patients diagnosed as BE were consecutively enrolled and most of them took continuous PPI. The 25 patients underwent endoscopic surveillance and received biopsy. If the specialized intestinal metaplasia (SIM) was lost at any poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…Additionally, a study directed to evaluate the regression of BE with proton pump inhibitors treatment showed that, in patients with lower degree of CDX2 expression, together with other markers, the chance for reversibility of BE was higher [26]. This study corroborates the role of CDX2 in esophageal epithelial pathologic differentia-tion and suggests biomarkers could predict the reversibility of this process.…”
Section: Discussionsupporting
confidence: 61%
“…Additionally, a study directed to evaluate the regression of BE with proton pump inhibitors treatment showed that, in patients with lower degree of CDX2 expression, together with other markers, the chance for reversibility of BE was higher [26]. This study corroborates the role of CDX2 in esophageal epithelial pathologic differentia-tion and suggests biomarkers could predict the reversibility of this process.…”
Section: Discussionsupporting
confidence: 61%
“…10 And, the hiatal hernia was endoscopically identified when the distance from the esophagogastric junction to the diaphragmatic impingement was more than 1 cm. 11 One expert endoscopist (N.K.)…”
Section: Gastroscopymentioning
confidence: 99%